1995
DOI: 10.1111/j.1651-2227.1995.tb13479.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physical growth, mental development and nutritional supplementation in stunted children: the Jamaican study

Abstract: The relationship between physical growth and change in mental development on the Griffiths mental development scales was investigated in 127 stunted Jamaican children over a 2-year period. The role of nutritional supplementation in this relationship was examined. There were no consistent associations between changes in weight-for-height or head circumference and developmental change. Height gain over 2 years was significantly associated with change in mental age, and locomotor and hearing and speech subscale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…In stunted Jamaican children aged between 6 and 24 months, change in height over the subsequent 24 months was associated with change in developmental levels. Furthermore, change in height in the first 12 months predicted change in mental age in the second 12 months even after controlling for height change in the second year 30 .…”
Section: Longitudinal Studies Of Undernourished Childrenmentioning
confidence: 89%
“…In stunted Jamaican children aged between 6 and 24 months, change in height over the subsequent 24 months was associated with change in developmental levels. Furthermore, change in height in the first 12 months predicted change in mental age in the second 12 months even after controlling for height change in the second year 30 .…”
Section: Longitudinal Studies Of Undernourished Childrenmentioning
confidence: 89%
“…The higher prevalence of deficiencies in iron and zinc may have contributed to these differences. Many studies have shown that among undernourished children, mental 34 -36 and motor development 37,38 are often below normal. The level of poverty may also contribute to the test results.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the present study, we attempted to disentangle the relationship between postnatal anthropometric status and PD among LBW children.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] There is only one study which explores the association between the three anthropometric indicators and psychomotor development (PD) but it did not control for any confounding factors. 15 In the present study, we attempted to disentangle the relationship between postnatal anthropometric status and PD among LBW children.…”
Section: Introductionmentioning
confidence: 99%